From Commitment to Rhetorical Creativity: An Approach to the Literary Dimensions of IbnBadis’s Writings. (مجلة إحالات, 2026)
This research explores the literary dimensions of Abdelhamid Ben Badis’s thought and hisrole in the Algerian cultural renaissance. It focuses on his prose and poetry—particularly his articlesand speeches—highlighting their artistic value and his mastery of Arabic rhetorical techniques. Thestudy emphasizes his use of Islamic heritage and eloquent language to address national issues andliberate Algerian youth from the superstitions and heresies promoted by colonial powers. It alsoexamines his pivotal role in founding the Association of Algerian Muslim Scholars on authentic Islamic foundations. His writings reflect the essence of the reform movement and stand as a form ofintellectual resistance to colonialism.